Accessible design: principles, challenges, and best practices - Melnychuk, Oleksandr (Запоріжжя: НБ ТДАТУ, 2025)
Accessibility refers to the practice of designing products and experiences that are usable by all individuals, regardless of their physical or cognitive abilities (World Wide Web Consortium [W3C], 2018). It is fundamentally about fostering inclusion, ensuring that no individual is excluded from utilizing digital tools or services. Accessibility goes beyond mere legal compliance; it seeks to uphold the principle that digital experiences should be available to all.
Keywords: accessible design; cognitive disabilities; visual disabilities; accessibility principles